PENGELOLAAN KEUANGAN NEGARA HASIL TINDAK PIDANA KORUPSI BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2003 TENTANG KEUANGAN NEGARA (STUDI PUTUSAN MAHKAMAH AGUNG 29/PID.SUS-TPK/2021/PN.JKT PST): Management of State Financial Proceeds of Corruption Crime based on Law Number 17 of 2003 Concerning State Finance State ( Study of Supreme Court Decision 29/Pid.Sus-TPK/2021/PN.Jkt. Pst) - Marzani, Devica Alivia; Edward, Ferry (Faculty of Law, Universitas Trisakti, 2024)
In the Supreme Court decision 29/Pid.Sus-TPK/2021/PN.Jkt.Pst the panel of judges decided that Juliari Peter Batubara must pay state compensation money. The main issues raised by the author 1) What is the process for managing returns to state finances resulting from criminal acts of corruption (Study of Supreme Court Decision 29/Pid.Sus-TPK/2021/PN.Jkt.Pst), to the state according to the applicable laws and regulations? 2) Are there any obstacles in the process of recovering state financial losses from corruption? This study uses a normative research type that is descriptive-analytical. Data collection uses primary data and secondary data. The data is processed qualitatively by drawing conclusions using a deductive method. The results of the research show that the process of managing state financial losses carried out by the defendant Juliari Peter Batubara refers to the Attorney General's Office Regulation of the Republic of Indonesia Number 19 of 2020 concerning Settlement of Compensation Money Decided by Courts and Regulation of the Minister of Finance Number 225 of 2020 concerning the Electronic State Revenue System . In the process of returning state financial losses resulting from the corruption crime of Juliari Peter Batubara there were no obstacles because the convict was able to and had compensated for the state losses arising from the proceeds of the corruption crime.